Indikator Penyebab Praktik Korupsi Pada Industri Konstruksi Di Sumatera Barat - vivi ariani; Dwifitra Y. Jumas; Wahyudi P. Utama; Wenny W. Wahyudi (Rekayasa Sipil, 2023)
The main objective of this research is to identify and analyze indicators of the causes of corrupt practices in the construction sector in West Sumatra. Research methodology used descriptive statistics and inferential statistical analysis used in the test is Cronbach's Alpha. The results of Cronbach's Alpha test can be seen in the value in the Corrected Item-Total Correlation column for the number of variables as many as 30 can be seen in r table 0.361. This is also supported by Cronbach's alpha value of 0.960. The indicator that causes corruption in the first rank is the existence of tender evaluations that do not meet the criteria (X9). Conclusion in this research are 10 variables (out of 30 variables) indicators of the causes of corrupt practices in construction projects in West Sumatra.